2018
DOI: 10.3892/or.2018.6250
|View full text |Cite
|
Sign up to set email alerts
|

The targeted inhibition of Hsp90 by a synthetic small molecule, DPide offers an effective treatment strategy against TNBCs

Abstract: Triple-negative breast cancers (TNBCs) are the most aggressive and metastatic subtype of breast cancers and exhibit poor clinical outcome due to the lack of drug target receptors such as estrogen receptors (ER), progesterone receptors (PR), and human epidermal growth factor receptor 2 (Her2). The limited effectiveness of therapeutic options and the poor prognosis of TNBC patients emphasize the urgent need for identifying new therapeutic agents. In this regard, heat shock protein 90 (Hsp90) has emerged as a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…This can also be visulaized in its uniform electron density distribution via MEP plot. It was found that the both the B 15 GeN 16 and B 15 SiN 16 nanocages showcase a local structural deformation around the Ge and Si sites, which is in agreement with the results obtained in previously published experimental and theoretical studies [55][56][57][58][59][60]. The newly formed Ge-N and Si-N bonds are about 1.893 Å and 1.774 Å in vacuum environment and 1.900 Å and 1.778 Å in solvent environment as the Ge and Si atoms are projected out of the nanocage surfaces [61].…”
Section: Resultssupporting
confidence: 91%
“…This can also be visulaized in its uniform electron density distribution via MEP plot. It was found that the both the B 15 GeN 16 and B 15 SiN 16 nanocages showcase a local structural deformation around the Ge and Si sites, which is in agreement with the results obtained in previously published experimental and theoretical studies [55][56][57][58][59][60]. The newly formed Ge-N and Si-N bonds are about 1.893 Å and 1.774 Å in vacuum environment and 1.900 Å and 1.778 Å in solvent environment as the Ge and Si atoms are projected out of the nanocage surfaces [61].…”
Section: Resultssupporting
confidence: 91%